Evolutionary and Constructive Perspectives of Organization in Organizational Learning - Ahumada Figueroa, Luis (Revista de Psicología, 2002)
The main objective of this paper is to expand the organizational learning analysis framework according to the relationship between the organizational learning and organizational environment. From a constructivist and evolutionist perspective of the organization with emphasis in the emerging processes, it is developed and discussed that the ability to learn faster than the competitors would be the only source of competitive advantage sustainable in time. On the other hand, it is analyzed the concept of “dominating logic” as a useful framework for an explanation about how the management strategy and the organizational learning suppose a modification of this logic in order to obtain a better adaptation to the environment changes. Finally, it is stated that the main challenge for firms and organizations nowadays, is the creation of culture and climate that facilitate the organizational learning in a turbulent environment.